Do headaches impact pregnancy planning behaviors? A cross-sectional school-based study in Japan - Masahito Katsuki; Yasuhiko Matsumori; Muneto Tatsumoto; Keisuke Suzuki; Daiki Sato; Koki Kikugawa; Shigeharu Kamado; Siobhán O’Connor; Kieran Moran (The Journal of Headache and Pain)
Abstract Objective Headache disorders are a common neurological disease with socioeconomic burdens among individuals of reproductive age, yet little is known about its impact on fertility intentions. This study examined the association between headache characteristics and fertility intention among parents of school-aged children with headaches in Japan. Methods We prospectively conducted a school-based online survey for students’ parents in Tsubame City, Japan, in 2024. We asked about their age, sex, headache characteristics, the use of acute and prophylactic medications; monthly headache days (MHD); monthly acute medication intake days (AMD); Headache Impact Test-6 (HIT-6); Migraine Interictal Burden Scale-4 (MIBS-4); and the number of children. We also examined the impact of headaches on pregnancy plans by asking, “Are you avoiding or have you avoided pregnancy due to headaches?” and those who answered “yes” to this question were defined as the “avoid pregnancy group.” Results Of the 5,227 households, we received 1,127 (21.6%) responses, and 599 responses from parents with headaches were analyzed. The median (first quartile-third quartile) age was 43 (40–48) years, and 562 (93.8%) were female. They reported median MHD: 3 (1–4) days, AMD: 3 (1–6) days, HIT-6: 60 (58–68), and MIBS-4: 4 (2–8). Fifty (8.3%) used prophylactic medications, and 492 (82.1%) used acute medications for headache attacks. The median number of children was 2 (2–2). Twenty-two of the 562 female respondents (3.9%) answered that they were avoiding or had avoided pregnancy due to headaches. Both the HIT-6 score (median 58 [53–64] vs. 63 [59–66], p = 0.033) and the MIBS-4 score (4 [2–7] vs. 6 [4–7], p = 0.012) were significantly higher in the avoid pregnancy group. Multivariable analysis showed that avoid pregnancy group was significantly associated with: older age (odds ratio [OR] 1.16, 95% confidence interval [CI]: 1.05–1.29, p = 0.004), shorter headache duration (OR 0.91: 95%CI 0.85–0.98, p = 0.016), and a greater number of MHD (1.08, 95%CI: 1.01–1.16, p = 0.031), the presence of nausea or vomiting (OR 6.11, 95%CI: 1.46–25.60, p = 0.013), and phonophobia (OR 6.40, 95%CI: 1.71–23.99, p = 0.006). The avoid pregnancy group was more likely to express concerns about disability during pregnancy, parenting, and potential harm from medications. Conclusions Some of the respondents were avoiding or had avoided pregnancy because of their headaches. Those in the avoid pregnancy group had both ictal and interictal severe headache burden and felt that headache disorders negatively affected fertility intention.